ANALYSIS OF THE PROBLEM OF MANAGEMENT FUNCTION OF EDUCATION SYSTEM IN UNDERDEVELOPED ELEMENTARY SCHOOLS (SD) - Agus Setiawan; Siti Inganah (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
Basic education in disadvantaged areas in Indonesia faces various challenges that hinder its development and quality. This study aims to identify the main issues in the management of education in primary schools (SD) in disadvantaged areas and provide recommendations for improvement. Using a qualitative approach and case study method, this research examines four key factors influencing the quality of education: the limitations of infrastructure and facilities, the quality of educators, access to learning materials, and community participation. The findings indicate that limited physical facilities, including inadequate school buildings, poor sanitation facilities, and limited access to technology, are significant obstacles to the learning process. In addition, the low quality of teachers, who often do not meet the required educational qualifications, and the lack of motivation and professional development for teachers, exacerbates the problem of educational quality. The lack of access to adequate learning materials and the limited community involvement in education management are also contributing factors. This study recommends improving educational facilities, providing teacher training, and enhancing community participation in education to create more inclusive and quality education in disadvantaged areas.